Avaliação da resistência de genótipos de milho pipoca à lagarta-do-cartucho, Spodoptera frugiperda (J.E.Smith) (Lepidoptera: Noctuidae) - Sanches, Rafael Egéa (2014)
The objective of this study was to find and characterize sources of resistance in popcorn compared to S. frugiperda, which can be used in genetic breeding. The experiments were conducted in the laboratory of Entomology Iguatemi Experimental Farm at the State University of Maringá - UEM. The vegetal material were fifteen leafy popcorn maintained by the plant breeding program of the UEM and three commercial checks, IAC 125, BRS 1030 and Zapalote Chico. The test was developed in ICD, and observed: larval period, final weight of caterpillars, total mass of caterpillars, average weight of caterpillars, larval viability, pupal period, pupal viability, pupal mass, adult viability, emergence of deformed adults, male/female ratio, number of eggs per female, eggs viability, area and leaf mass ingested. A global analysis of the results indicates that genotypes with high potential as a source of resistance to fall armyworm are BOZM 260 , BRS 1030, PA 091, PARA 172 and UNB - 2U C4.